Town Councils as Policy Instruments for Community Engagement: Local Diversity Within a Centralized Response to the COVID Pandemic in England - Susan Ball (Revue Française de Civilisation Britannique)
During the time of successive lockdowns due to the COVID pandemic, local organisations faced increased demand for ensuring that residents and businesses were kept informed and supported while simultaneously waiting for guidance to be passed down from central government to local authorities and on to communities. These community-based organisations include 10,000 town councils comprising the lowest level of government of England and covering 40% of the population. This article introduces town councils as policy instruments theorized from a political sociology perspective. It outlines the recent historic context of town councils in terms of national policy aimed at developing community engagement, with particular focus on the introduction of the localism agenda by the Coalition Government through to policies of austerity since 2010 and levelling up since 2019. This shows the lack of goals or consensus on the role of town councils, which function as policy instruments connected to policy for community engagement in a symbolic way and having limited expectations in terms of implementation. The article then addresses central government guidance to local authorities in the context of the COVID pandemic and lockdowns. The response of two town councils to the delays and confusion arising from the process of translation by ministers and Whitehall officials of directions from Downing Street is described. By means of the reflective hindsight provided in interviews with town councillors in two case studies, the role of town councils as policy instruments in developing community engagement during the pandemic is outlined. The article concludes on the case studies viewed as policy instruments set in the wider context of policy discourse on localism.